The Implementation in Teaching Direction of Problem Based Learning at Junior State 1 Sumber - Ana Latifah Tuzzahro; Ikariya Sugesti; Fitri Aprianti (National Conference on Language, Education, and Technology Proceeding, 2023)
This study aims to determine the implementation of teacher learning using the problem based learning model. The focus of this research is the implementation of Problem Based Learning in Teaching Direction  At Junior State 1 Sumber. Data collection techniques are observation techniques, interviews, documentation. Data collection tools are observation sheets, interview guides, and documentation. Data processing was carried out using a qualitative descriptive analysis. The results of the study show that the learning gain of students increases and is well done by using this learning model. The validity of the data used is source triangulation and technique triangulation. Research results from the Implementation Problem Based Learning in Teaching Direction At Junior State 1 Sumber 1) Planning includes preparing learning tools and selecting learning materials. 2) Implementation includes, conveying learning objectives, dividing groups, guiding discussions, presenting the results of discussions. And evaluate the results of the discussion.